Nannochloropsis oceania-derived defatted meal as an alternative to fishmeal in Atlantic salmon feeds - Sørensen, Mette; Gong, Yangyang; Bjarnason, Fridrik; Vasanth, Ghana Kalerammana; Dahle, Dalia; Huntley, Mark; Kiron, Viswanath (PLOS ONE, 2017)
publishedVersion